Stature estimation of an individual using nasal, facial, and palatal height among Tamil Nadu population - J Dinakaran; P Hariganesgh; S Shamala; K Dhivya; V Saranya; M Saranya (Wolters Kluwer Medknow Publications, 2021)
Background: Stature estimation in human identification has a significant forensic importance. The stature correlates positively with bones or human body parts. Measurements of various body parts such as the arm, leg, feet, and finger can be used to estimate stature. This study is done to correlate the stature of person with facial, nasal, and palatal height among Tamil Nadu population. Aim and Objective: The aim and objective was to determine an individual's stature using facial, nasal, and palatal height and to find out the most reliable parameter to determine the stature of the person. Materials and Methods: Anthropometer, Vernier caliper, and palatometer were used for the analysis. The initial pilot study included 20 individuals. The representative study included 100 individuals of age 21-25 years. (Group 1 - males, Group 2 - females). Values of the three parameters (nasal, facial, and palatal) are calculated and related to that of the person's stature. Results: The quantitative data collected from the subjects are studied using (Pearson correlation) statistical analysis. The quantitative data availed from nasal height were found to be more reliable compared to the other two data in stature prediction. Correlation between stature and nasal height shows a significant positive correlation among the female group (2) with (P- value = 0.57). Conclusion: This study may play a significant role in case of human identification immediately after mass disasters and certain criminal investigations. Further studies with larger samples may produce more reliable values.